Iodine doping of amorphous carbon thin films deposited using camphoric carbon precursor / Dayana Kamaruzaman - Kamaruzaman, Dayana (2013)
Amorphous carbon (a-C) is expected to be an excellent material for fabricating low cost and high efficiency carbon based solar cells because of its interesting properties and feasibility of band gap engineering over a wide range. The preparation of a-C thin films was carried out by using thermal chemical vapor deposition (CVD) technique. The initial phase of this work involved the deposition of a-C thin films using camphor oil as an environmentally carbon precursor. The second phase is focused on the doping process of a-C thin films with iodine (I) as p-type dopant. The studies were done to determine the optimum parameters to obtain a p-type a-C:I thin film. The deposition temperature, deposition time and gas flow rate effects on the properties of a-C thin films were analyzed in details. The a-C thin films deposited at 550°C, 30 min and 35 seem were considered as the best parameters throughout this work . For doping process, the a-C:I thin films is found to be influenced by doping temperature, amount of iodine and doping time effects. Based on the results, the a-C:I thin film prepared at 400°C, l.Og and 10 min can be considered as the optimized parameter to produce higher conductivity (-10' S.cm’ ) and lower optical band gap. The optimum preparation parameters for a-C and a-C:I thin films have been identified. Comparison between without and with iodine doping on a-C thin film properties have also been studied. Hetero-junction of both films fabricated with n-Si found photovoltaic behavior.